2010
DOI: 10.14499/indonesianjcanchemoprev1iss2pp78-84
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Solanum nigrum L. Herb Ethanolic Extract and Doxorubicin Performs Synergism on T47D Breast Cancer Cells

Abstract: Leunca (Solanum nigrum L.) has been proven to possess anticancer activity on some type of cancer cells. In vitro study of solamargine found in the herb showed cytotoxic effect against several breast cancer cell lines, such as T47D and MDA-MB-31. Hence, further study on its potential as a co-chemotherapeutic agent needs to be conducted, in order to overcome resistance problem commonly found in cancer chemotherapy. This study aimed to examine the cytotoxic activity of leunca herb ethanolic extract (LEE) alone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The methanolic extract of S. nigrum L. fruit exhibited cytotoxicity activity significantly higher on HeLa cell than on Vero normal cell (Patel et al, 2009). The equivalent combination of S. nigrum L. ethanolic extract with doxorubicin performed synergism anticancer effect on T-47D breast cancer cells (Anindyajati et al, 2010). Both S. nigrum L. leaves and stems methanolic extracts also demonstrated as an anticancer agent on PC3 prostate and HeLa cervical cancer cells.…”
Section: Discussionmentioning
confidence: 87%
“…The methanolic extract of S. nigrum L. fruit exhibited cytotoxicity activity significantly higher on HeLa cell than on Vero normal cell (Patel et al, 2009). The equivalent combination of S. nigrum L. ethanolic extract with doxorubicin performed synergism anticancer effect on T-47D breast cancer cells (Anindyajati et al, 2010). Both S. nigrum L. leaves and stems methanolic extracts also demonstrated as an anticancer agent on PC3 prostate and HeLa cervical cancer cells.…”
Section: Discussionmentioning
confidence: 87%
“…We investigated the cytotoxic of DOX and used it for reference of combination with SNE. Based on previous research, a combination of leunca with several chemotherapy agents has been known to increases the cytotoxic of chemotherapy agents in several cancer cells (Sarmoko, et al, 2011;Istiaji, et al, 2010;Maruti, et al, 2011;Anindyajati, et al, 2010). The combination of SNE with DOX increased the cytotoxicity of DOX, reduced the cell viability and proliferation of MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that Leunca herb extract is potential to be developed as a chemopreventive agent due to its activity on some cancer cell lines, such as MCF-7, T47D, and HeLa cells. The extract could enhance cytotoxic effects of doxorubicin on MCF-7 and T47D breast cancer cells and also could increase cytotoxic effects of cisplatin on HeLa cervical cancer cells (Princess, et al, 2010;Anindyajati, et al, 2010, andIstiaji, et al, 2010). Solanine and solamargine are known as main active compounds that have cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%